The oxytocin signalling gene pathway contributes to the association between loneliness and cardiometabolic health. (September 2021) - Winterton, A.; Bettella, F.; Beck, D.; Gurholt, T.P.; Steen, N.E.; Raadevand, L; Westlye, L.T.; Andreassen, O.A.; Quintana, D.S.
Abstract : Increasing evidence has shown adverse effects of loneliness on cardiometabolic health. Oxytocin has been linked with social cognition and behaviour, however, recently also with energy metabolism and obesity suggesting that oxytocin may underlie common mechanisms bridging mental and somatic traits. To clarify whether the oxytocin system contributes to the links between cardiometabolic health and loneliness, we calculated the genetic contribution of single nucleotide polymorphisms in the oxytocin pathway to the polygenic architecture of loneliness and body mass index (BMI) and their associations with body composition (body MRI and bone mineral density), blood markers, and blood pressure. We compared such contribution to those of 100 random gene-sets in the UK-Biobank. Our analysis revealed significant (all FDRs below.05) associations of an oxytocin-pathway polygenic score (PGS) for BMI with abdominal subcutaneous fat, HDL, triglycerides, lipoprotein(a), and bone mineral density, as well as between an oxytocin PGS for loneliness and apolipoprotein A1. These results provide evidence for the oxytocin signalling pathway's role in energy homeostasis, lipid metabolism and storage, and bone density, and for oxytocin's pleiotropic effects.